A Case Study of Factors that Influenced the Attrition or Retention of Two First-Year Special Education Teachers - Grant, Marquis C. (Journal of the American Academy of Special Education Professionals, 2017)
The issue of attrition and retention has been a chronic problem in the field of education for decades. School districts across the United States are experiencing shortages of qualified special education teachers largely due to high turnover rates, with many of these teachers electing not to return after their first year of teaching. In fact, roughly nine percent of special educators not return to the profession after their first year, citing themes such as lack of administrative support, excessive paperwork and burnout as primary factors that prompted their decision to leave. The purpose of this study was to identify problems faced by two novice special educators from their own perspective. Further analysis of the research data produced additional themes, including poor co-teaching relationships, the use of ineffective co-teaching models, student behavior, time management, paperwork, isolationism, time management, ambiguous special education practices and procedures.